Function of L-Pipecolic Acid as Compatible Solute in Corynebacterium glutamicum as Basis for Its Production Under Hyperosmolar Conditions - Pérez-García, Fernando; Brito, Luciana F.; Wendisch, Volker F. (Frontiers in Microbiology, 2019)
Pipecolic acid or L-PA is a cyclic amino acid derived from L-lysine which has gained interest in the recent years within the pharmaceutical and chemical industries. L-PA can be produced efficiently using recombinant Corynebacterium glutamicum strains by expanding the natural L-lysine biosynthetic pathway. L-PA is a six-membered ring homolog of the five-membered ring amino acid L-proline, which serves as compatible solute in C. glutamicum. Here, we show that de novo synthesized or externally added L-PA partially is beneficial for growth under hyper-osmotic stress conditions. C. glutamicum cells accumulated L-PA under elevated osmotic pressure and released it after an osmotic down shock. In the absence of the mechanosensitive channel YggB intracellular L-PA concentrations increased and its release after osmotic down shock was slower. The proline permease ProP was identified as a candidate L-PA uptake system since RNAseq analysis revealed increased proP RNA levels upon L-PA production. Under hyper-osmotic conditions, a ΔproP strain showed similar growth behavior than the parent strain when L-proline was added externally. By contrast, the growth impairment of the ΔproP strain under hyper-osmotic conditions could not be alleviated by addition of L-PA unless proP was expressed from a plasmid. This commensurate with the view that L-proline can be imported into the C. glutamicum cell by ProP and other transporters such as EctP and PutP, while ProP appears of major importance for L-PA uptake under hyper-osmotic stress conditions.